Emerging Role of Molecular Testing in the Management of Non-metastatic Non-small Cell Lung Cancer - Hidenori Kage (Tuberculosis and Respiratory Diseases)
Advances in targeted therapies and immune checkpoint inhibitors have significantly enhanced survival rates for patients diagnosed with metastatic non-small cell lung cancer (NSCLC). In non-metastatic NSCLC, adding immune checkpoint inhibitors postchemoradiotherapy has led to improved outcomes in stage III disease and during the perioperative period for stages IB–IIIA. Recently, adjuvant osimertinib and alectinib therapy have demonstrated improved survival rates for patients with epidermal growth factor receptor (EGFR) or anaplastic lymphoma kinase (ALK) alterations, respectively; these therapies are now considered standard treatments. Additionally, osimertinib has shown efficacy when administered postchemoradiotherapy in stage III NSCLC. These findings emphasize the importance of assessing EGFR and ALK status to accurately guide treatment decisions for nearly all NSCLC patients, whether they are undergoing curative surgery, chemoradiotherapy, or receiving palliative chemotherapy. This review summarizes recent trials on perioperative and postchemoradiation therapy and advocates for the necessity of molecular testing in non-metastatic NSCLC to enhance patient outcomes.